Curriculum Reforms and Competence Level of High School Agriculture Teachers in Swaziland - Sandile B. Ndwandwe; Barnabas M Dlamini (Journal of International Agricultural and Extension Education, 2013)
A descriptive study was designed to determine competence level of high school agriculture teachers regarding curriculum reforms in Swaziland. The major objective of the study was to compare the International General Certificate of Secondary Education (IGCSE) and Swaziland General Certificate of Secondary Education (SGCSE) agriculture syllabi using content analysis procedure in terms of objectives, content topics contained in the syllabi, learning approaches used, available teaching facilities and assessment used. In this study, information from content analysis revealed that the SGCSE agriculture syllabus was similar to the IGCSE agriculture syllabus in some aspect and dissimilar in other aspects. The findings indicated that the SGCSE agriculture curriculum had three more objectives, and had more content topics which were responsive to the socio-economic challenges of the country. The IGCSE and SGCSE agriculture curricular had similar teaching facilities and similar teaching and learning approaches as they are both student-centered and skill based. It can be concluded that the new objectives and new topic contents incorporated into the SGCSE agriculture syllabus has created a gap in terms of knowledge base possessed by the high school agriculture teachers in Swaziland. There is a need for agricultural topics to change to reflect changing conditions in the environment and advances in technology. This is to enable high school agriculture teachers enhance their competencies in addressing the new objectives incorporated in the SGCSE agriculture syllabus, as well as teaching the new content topics incorporated in the SGCSE agriculture syllabus.
Keywords: Competence; Content Analysis; Curriculum; High School Agriculture Teachers; IGCSE Agriculture; SGCSE Agriculture